AGGREGATE LITIGATION CASES IN BRAZIL: NOTEWORTHY CONSIDERATIONS ON THE AGGREGATION OF CASES, CLASS ACTIONS AND BINDING PRECEDENTS IN LITIGATIONS PURSUANT TO THE NEW CPC/2015 - Zaneti Júnior, Hermes (Revista de Direito Brasileira, 2019)
Brazilian law is experiencing intense transformation. Civil Procedural Law has incorporated the aggregate litigation model of adjudication as means to cope with the increasingly large volume of lawsuits, currently, more than 110 million cases. The aggregate litigation technique combines cases of identical procedural or subject matter nature and submits them to a joint trial by filing a chosen leading case. This adjudicating technique is applicable to ongoing lawsuits of individual or class nature, pursuant to the CPC, which foresees two different scenarios: the aggregate claims (IRDR) and the aggregate appeals of either infra constitutional or constitutional matter. For a fair process to be ensured, the relationship between aggregate litigation and class actions cases, as well as the relationship between aggregate litigation and the establishment, application and overruling of binding precedents require the development of appropriate techniques and tools.